(3GdGfJUGQ Ydi YdeGA GdCeUGQs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s ((3eUQ s)
(3ChdgG (B:s
(3GdQcf GdKGfi ai HjGf ef jLH Ydjge GdbSGeI hef dGjLH Ydjge s
(3BNQgG (B:s
(3ai HjGf eG jJYdb HGdebGe ai GdCecfI hGdHbGY hGdEfJbGd YfgG , hgh eTJed Ydi eSGFd GdeSCdI GdKGdKI ai LhGR GdebGe ai GdHdO hgPG BNQ cdGefG ai GdEfJUGQ Je GdSaQ GdKGef YTQ s
(3GdfSNI HgG MhGTs
(3fSNI eUMMIs
(3cJHJ YfGhjjf GdaUhd hGdahGJM HGdNW GdSejc ef hba GdeDda s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
Keywords: (3GNJdGa GdabgGAs